The genotype and phenotype of chromosome 18p deletion syndrome: Case series. Issue 18 (7th May 2021) - Jin, Qiujie; Qiang, Rong; Cai, Bo; Wang, Xiaobin; Cai, Na; Zhen, Shuai; Zhai, Wen
Abstract: Rationale: The chromosome 18p deletion syndrome is a syndrome with a deletion of all or a portion of the short arm of the chromosome 18. The phenotypes of the chromosome 18p deletion syndrome vary widely among individuals due to differences in size and breakpoints and the involved genes on the deletions. Given the varied and untypical clinical presentation of this syndrome, the prenatal diagnosis of the syndrome still presents as a challenge. Patient concerns: We described 4 China cases with different chromosomal breakpoints. In case 1, a woman who with mild phenotypes gave birth to a severely deformed fetus. Three other cases were for prenatal diagnosis. Their phenotypes are the increased nuchal translucency (INT) and the noninvasive prenatal testing (NIPT) indicated deletions on the chromosome 18p and severe hydronephrosis respectively. Diagnosis: The 4 cases were diagnosed with chromosome 18p deletion syndrome through karyotype analysis and array-based comparative genomic hybridization (array-CGH). Interventions: Karyotype analysis and array-based comparative genomic hybridization were used to analyze the abnormal chromosome. Outcomes: Case 1 and case 2 revealed 11.51 and 12.39 Mb deletions in 18p11.32p11.21. Case 3 revealed 7.1 Mb deletions in 18p11.3218p11.23. Case 4 revealed 9.9 Mb deletions in 18p11.3218p11.22. Lessons: In our report, we are the first to report that mother and progeny who have the same chromosomal breakpoint have different phenotypes, significantly. In addition, we found a new phenotype of chromosome 18p deletion syndrome in fetus, which can enrich the phenotypes of this syndrome in the prenatal diagnosis. Finally, we demonstrate that the individuals with different chromosomal breakpoints of 18p deletion syndrome have different phenotypes. On the other hand, the individuals with the same chromosomal breakpoints of 18p deletion syndrome may also have remarkably different phenotypes.